2017
DOI: 10.7869/djo.304
|View full text |Cite
|
Sign up to set email alerts
|

Spectacles and Refractive Errors: Children’s Perspective

Abstract: Purpose:-To study common perceptions in children about the use of spectacles as well as refractive error and problems faced by these children while using spectacles. Methods:-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Even though their children wore glasses, they were worried about its acceptance in the family as well as at school. Similar tendencies have been reported from other parts of the world 13,18,[25][26][27][28] . Hence, there is a need of communication intervention to be planned by the concerned authorities to educate parents.…”
Section: Discussionsupporting
confidence: 88%
“…Even though their children wore glasses, they were worried about its acceptance in the family as well as at school. Similar tendencies have been reported from other parts of the world 13,18,[25][26][27][28] . Hence, there is a need of communication intervention to be planned by the concerned authorities to educate parents.…”
Section: Discussionsupporting
confidence: 88%
“…However there are many psychosocial perceptions about the wearing of spectacles among people especially young adults. [6][7][8][9][10][11] Generally, ignorance of refractive errors and the benefits of using spectacles to relieve symptoms could be said to be one of the main causes of not wearing spectacles. 12,13 People who need spectacles also shy from wearing them because they would be thought of as being blind or visually handicapped.…”
Section: Introductionmentioning
confidence: 99%
“…For others, wearing spectacles could diminish their chances of getting a spouse whereas some also perceive it to be for only the old folks. 9,12,14 Contrary to the above perceptions, people wear spectacles because it improves their appearance and sight; augments their confidence and demeanour; and makes them look innocent and intelligent. 12,15,16 Most psychosocial perceptions to spectacle wear, however, usually results non-use of spectacles.…”
Section: Introductionmentioning
confidence: 99%
“…In India, it is acknowledged that access to primary eye care facilities is not uniform across the country, 6,7 especially in children 8,9 who remain at risk of having visual impairment specifically due to causes such as uncorrected refractive errors 10 . Others have reported that programmes that cater to school‐aged children to alleviate needless visual impairment due to uncorrected refractive errors are influenced by local circumstances such as geographical location, availability of resources, social beliefs and economic conditions 10–17 . Therefore, the knowledge of local circumstances and their influence on school eye health programmes will enable better planning, administration, monitoring and evaluation of the programme and promote its scalability.…”
Section: Introductionmentioning
confidence: 99%